Adaptation of a waste water treatment system in the urban community of Lacabamba, Ancash region-Peru, using the artificial wetlands technology - Lovera, Daniel (2006)
The present investigation was a project selected in 2003 that aimed to implement and evaluate the comprehensive wastewater management system in the urban community of Lacabamba, Ancash region, by using the artificial wetland system to treat water and its reuse. in a communal bio-garden, as an innovative technology to reduce contamination of surface water sources; protect the health of the inhabitants and avoid deterioration of the environment; as well as involving the population in its 2015 Sustainable Development Plan for the Lacabamba district and actively participating in the awareness-raising and training programs of the Research project. The call was made by the Small Competitive Research Fund Program of the Secretariat for Environmental Management for Latin America and the Caribbean, SEMA / EMS and the International Development Research Center, IDRC of Canada, and focused on the sustainable use of water in the urban areas.